2000
DOI: 10.1046/j.1365-2222.2000.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 generation in atopic children following oral Lactobacillus rhamnosus GG

Abstract: Oral Lactobacillus rhamnosus GG ingestion for 5 days to 4 weeks has been shown to alleviate clinical symptoms of gastrointestinal inflammation and atopic dermatitis. To determine whether oral Lactobacillus rhamnosus GG may act by generating immunosuppressive mediator in atopic children. Lactobacillus rhamnosus GG (ATCC 53103) at a daily dose of 2 x 1010 cfu was added for 4 weeks to the diets of nine children (mean age, 21 months) with atopic dermatitis. Blood and faecal samples were collected before supplement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
226
5
7

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(246 citation statements)
references
References 24 publications
8
226
5
7
Order By: Relevance
“…26) Pessi and colleagues reported that oral administration of L. rhamnosus GG can alleviate the clinical symptoms of AD through the enhanced IL-10 production. 27) Subcutaneous injection of TGF-β 1 was reported to suppress the development of AD-like skin lesions in NC/Nga mice, which was accompanied by the reduction of IgE production. 28) Moreover, heat-killed L. brevis SBC8803 can suppress picryl chloride-induced AD-like skin lesions in NC/Nga mice due to the down-regulation of Th1 and Th2 response through the increased secretion of IL-10 and TGF-β 1 .…”
Section: Cd25mentioning
confidence: 99%
“…26) Pessi and colleagues reported that oral administration of L. rhamnosus GG can alleviate the clinical symptoms of AD through the enhanced IL-10 production. 27) Subcutaneous injection of TGF-β 1 was reported to suppress the development of AD-like skin lesions in NC/Nga mice, which was accompanied by the reduction of IgE production. 28) Moreover, heat-killed L. brevis SBC8803 can suppress picryl chloride-induced AD-like skin lesions in NC/Nga mice due to the down-regulation of Th1 and Th2 response through the increased secretion of IL-10 and TGF-β 1 .…”
Section: Cd25mentioning
confidence: 99%
“…Clearly, there is accumulating evidence that lactobacilli possess properties that are beneficial in a diverse range of diseases, including infections, allergy and cancer [3][4][5][6][7][8]. However, due to the diversity of species within the Lactobacillus genus not each Lactobacillus strain possesses similar health stimulating properties.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, as described by Lilly and Stillwell (4), are living microorganisms with low or no pathogenicity that exert beneficial effects on the health of the host. In human clinical trials the non-pathogenic Gram-positive commensal Lactobacilli found in the human and mouse gastrointestinal tracts have been considered as probiotics with beneficial health effects, including enhanced lymphocyte proliferation (5), innate and acquired immunity (6), and anti-inflammatory cytokine production (7). Lactobacillus rhamnosus GG (LGG), 1 a bacterium used in the production of yogurt, is one of the best-studied probiotic bacteria in clinical trials.…”
mentioning
confidence: 99%
“…Several Lactobacillus strains prevent or attenuate intestinal inflammation in the interleukin (IL)-10 Ϫ/Ϫ mouse model, which spontaneously develops enterocolitis (15,16). LGG increases anti-inflammatory IL-10 levels in children (7). Furthermore, LGG has been suggested as adjunctive therapy for Crohn's disease (17).…”
mentioning
confidence: 99%